Green cosmetics via bio-oil - Cappoen, Laurens; Deconinck, Pieter; Ras, Kevin De; Saegher, Delphine De; Vernimmen, Axel (Student Undergraduate Research E-journal!, 2017)
The refining of crude vegetable oil results in an unused sidestream, the oil deodorizer distillate (ODD). This distillate contains valuable ‘minors’, like squalene, tocopherols and sterols, which have applications in the cosmetic, pharmaceutical and nutrition industry. Therefore, their successful separation from this sidestream increases the viability of a refinery. The separation is achieved by supercritical esterification and supercritical CO2 extraction. The objective of this study is to simulate the process with Aspen® and model the kinetics with AVS®. Different ODD are investigated with HT soybean giving the highest yield. Additionally, an economic analysis is performed to estimate the process profitability.